Improving the quality of healthcare by aroma essential oil / Muhammad Syafiq Abdul Razak - Abdul Razak, Muhammad Syafiq (Faculty of Art and Design, 2020)
Essential oils are compounds derived from plants, which catch the fragrance and taste of the plant, which is also called its "essence".